1998
DOI: 10.1029/98wr00003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of seven geostatistically based inverse approaches to estimate transmissivities for modeling advective transport by groundwater flow

Abstract: Abstract. This paper describes the first major attempt to compare seven different inverse approaches for identifying aquifer transmissivity. The ultimate objective was to determine which of several geostatistical inverse techniques is better suited for making probabilistic forecasts of the potential transport of solutes in an aquifer where spatial variability and uncertainty in hydrogeologic properties are significant. Seven geostatistical methods (fast Fourier transform (FF), fractal simulation (FS), lineariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(192 citation statements)
references
References 60 publications
(3 reference statements)
2
180
0
4
Order By: Relevance
“…Each realization derived in this way requires O d 2 N f computations. This can be considerably more e cient than alternative conditional simulation methods (such as those described in [19]), even when the log conductivity ®eld is Gauss±Markov and d is O N 0X5 f . The travel time example discussed in the next section illustrates both the estimation and conditional simulation aspects of the multiscale approach.…”
Section: Vsy Rxmentioning
confidence: 99%
See 2 more Smart Citations
“…Each realization derived in this way requires O d 2 N f computations. This can be considerably more e cient than alternative conditional simulation methods (such as those described in [19]), even when the log conductivity ®eld is Gauss±Markov and d is O N 0X5 f . The travel time example discussed in the next section illustrates both the estimation and conditional simulation aspects of the multiscale approach.…”
Section: Vsy Rxmentioning
confidence: 99%
“…The travel times of wastes released from underground storage facilities to the accessible environment provide valuable information for assessing possible exposure risks. Travel time is particularly important in radioactive waste disposal applications, since the exposure level for any given constituent depends on the ratio of travel time to halflife [19]. When the factors controlling solute transport are highly variable and uncertain it is best to use probabilistic approaches to characterize travel times and related risks.…”
Section: The Travel Time Estimation Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures commonly used range from ad hoc trial-and-error methods to sophisticated mathematical/statistical inverse algorithms. In a recent and exhaustive study comparing seven inverse approaches to estimate parameters for flow and solute transport models (Zimmerman et al, 1998), the authors concluded that "…the most important factor for achieving a successful solution was the time and experience devoted by the user of the method". This underlines an important point that applies not only to inverse methods, but more importantly to groundwater models themselves: Comprehensive physically-based numerical models are powerful tools, and are increasingly being equipped with user-friendly graphical interfaces and instant post-processing utilities (plots, maps, summary reports, etc), but their proper use for analysis and decision support will continue to require on the part of the user some knowledge of the underlying processes and their interactions, of the mathematical representation of these processes via equations and parameters, and of the particular features of the computer implementation -these are elements that can make the difference between a successful simulation and a meaningless one.…”
Section: Parameter Estimation and Model Calibrationmentioning
confidence: 99%
“…Numerous methods are able to work with a variety of data and model types in hydrology, meteorology, and oceanography such as those in Kitanidis and Vomvoris 1983, Hoeksema and Kitinidis 1984, Dagan 1985, Gelhar 1986 Neuman 1986a;b;c , Ghil 1989, Carrera and Glorioso 1991 , Yangxiao et al 1991, Bennett 1992, Sun and Yeh 1992, Courtier et al 1993 Daniel andWillsky 1997 andZimmerman et al 1998 . Many of the crucial issues in moving from theory to practice are well understood.…”
Section: Introductionmentioning
confidence: 99%